Clinical and Molecular Heterogeneity of Silver-Russell Syndrome and Therapeutic Challenges: A Systematic Review - Singh, Amit; Pajni, Ketan; Panigrahi, Inusha; Khetarpal, Preeti (Current Pediatric Reviews, 2023)
Background: Silver-Russell syndrome (SRS) is a developmental disorder involving extreme growth failure, characteristic facial features and underlying genetic heterogeneity. As the clinical heterogeneity of SRS makes diagnosis a challenging task, the worldwide incidence of SRS could vary from 1:30,000 to 1:100,000. Although various chromosomal, genetic, and epigenetic mutations have been linked with SRS, the cause had only been identified in half of the cases. Material and Methods: To have a better understanding of the SRS clinical presentation and mutation/ epimutation responsible for SRS, a systematic review of the literature was carried out using appropriate keywords in various scientific databases (PROSPERO protocol registration CRD42021273211). Clinical features of SRS have been compiled and presented corresponding to the specific genetic subtype. An attempt has been made to understand the recurrence risk and the role of model organisms in understanding the molecular mechanisms of SRS pathology, treatment, and management strategies of the affected patients through the analysis of selected literature. Results: 156 articles were selected to understand the clinical and molecular heterogeneity of SRS. Information about detailed clinical features was available for 228 patients only, and it was observed that body asymmetry and relative macrocephaly were most prevalent in cases with methylation defects of the 11p15 region. In about 38% of cases, methylation defects in ICRs or genomic mutations at the 11p15 region have been implicated. Maternal uniparental disomy of chromosome 7 (mUPD7) accounts for about 7% of SRS cases, and rarely, uniparental disomy of other autosomes (11, 14, 16, and 20 chromosomes) has been documented. Mutation in half of the cases is yet to be identified. Studies involving mice as experimental animals have been helpful in understanding the underlying molecular mechanism. As the clinical presentation of the syndrome varies a lot, treatment needs to be individualized with multidisciplinary effort. Conclusion: SRS is a clinically and genetically heterogeneous disorder, with most of the cases being implicated with a mutation in the 11p15 region and maternal disomy of chromosome 7. Recurrence risk varies according to the molecular subtype. Studies with mice as a model organism have been useful in understanding the underlying molecular mechanism leading to the characteristic clinical presentation of the syndrome. Management strategies often need to be individualized due to varied clinical presentations.
Keywords: macrocephaly